Ultrafine coal-based solid waste green grouting material based on double-gel synergy and preparation method of superfine coal-based solid waste green grouting material based on double-gel synergy

By forming a dual-gel synergistic system with ultrafine coal-based solid waste and ultrafine silicate cement, the performance deficiencies of existing grouting materials are solved, achieving a low-cost, high-efficiency green reinforcement effect, improving early and long-term strength, and reducing carbon emissions.

CN120903885APending Publication Date: 2025-11-07CHINA UNIV OF MINING & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511024109.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-24
Publication Date
2025-11-07

AI Technical Summary

Technical Problem

Existing single-gel grouting materials have performance deficiencies, especially cement-based materials which have high carbon emissions, low early strength, and insufficient durability, while coal-based solid waste materials have insufficient activity, leading to a decrease in the strength of composite materials, making it difficult to achieve efficient and green reinforcement.

Method used

A dual-gel synergistic system is formed by ultrafine coal-based solid waste and ultrafine silicate cement. Highly active powder is prepared through a multi-stage activation process. Through precise component ratio design, an interpenetrating network structure of CSH and NASH is formed. Combined with polycarboxylate superplasticizer and composite functional admixture, a balanced development of early and long-term strength is achieved.

Benefits of technology

It achieves low-cost, high-efficiency green grouting reinforcement, significantly reduces carbon emissions, improves early and long-term strength, solves the problem of insufficient activity of coal-based solid waste, and forms a dense interpenetrating network structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120903885A_ABST
    Figure CN120903885A_ABST
Patent Text Reader

Abstract

The invention discloses a superfine coal-based solid waste green grouting material based on double gel synergy and a preparation method, and relates to the technical field of grouting of geotechnical engineering and mining engineering. The material is prepared from 40-60 parts of superfine coal-based solid waste powder, 30-50 parts of superfine Portland cement, a Ca / Si ratio regulator, a polycarboxylic acid water reducer and a composite functional additive, coal gangue is activated through a multi-stage process of raw material screening, mechanical crushing, high-temperature calcination, superfine grinding, component optimization and chemical catalysis, high-activity powder with the particle size D95 being smaller than or equal to 10 microns and the active component being larger than or equal to 70% is formed, and the high-activity powder with the particle size D95 being smaller than or equal to 10 microns and the active component being larger than or equal to 70% is obtained. And compounding with superfine cement to form a C-S-H and N-A-S-H double-gel interpenetrating network. When the slurry is prepared, the water-cement ratio is controlled to be 0.35-0.55 through step-by-step stirring, and the apparent viscosity is smaller than or equal to 0.5 Pas. The material has both early strength and long-term strength, and is high in coal-based solid waste mixing amount and low in carbon emission. The performance bottleneck of a single gel system is broken through, efficient utilization of the coal gangue and green upgrading of the grouting material are achieved, and the grouting material is suitable for reinforcement and water plugging of geotechnical engineering such as mines and tunnels.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of geotechnical engineering and mining engineering grouting, and particularly relates to a superfine coal-based solid waste green grouting material based on double-gel synergy and a preparation method thereof. BACKGROUND

[0002] Grouting material is one of the key components in grouting technology. Grouting can play a role in water plugging and reinforcement mainly because the grouting material changes from a liquid phase to a solid phase (gelation) during grouting. Therefore, any substance that can change from a liquid (suspension, emulsion or solution) to a solid under certain conditions can generally be used as a grouting material. In grouting construction, the selection of one or more grouting materials will directly affect the success or failure of the grouting project and the technical and economic benefits. Currently, grouting materials are generally divided into two categories: one is particulate grouting material (mainly cement-based material), and the other is non-particulate grouting material (mainly chemical material). Among them, particulate grouting material generally has the advantages of abundant source, low price, environmental safety, and large-scale supply, and has become one of the main directions of the development of grouting materials.

[0003] The particulate grouting materials widely used in engineering at present mainly include portland cement and sulphoaluminate cement, but cement-based grouting materials have significant defects such as high carbon emission and insufficient durability (easily eroded by sulphate and shrinkage cracking). In recent years, the technology of preparing geopolymer grouting reinforcement materials by alkali activation of industrial solid waste has developed rapidly. This geopolymer grouting material has the advantages of low carbon, excellent environmental performance, and high long-term strength, but it has low early strength, strict requirements for raw material activity (existing technologies mainly focus on fly ash or slag, and the activation efficiency of low-activity coal gangue is low), and limited adaptability to complex geological environments, which restricts its engineering application. Therefore, it is urgent to seek new low-cost, high-performance, and resource-saving green grouting reinforcement materials to support the safe and efficient green development of national energy resources and the implementation of the "double carbon" goal.

[0004] In fact, the existing pure cement or pure geopolymer grouting reinforcement materials all belong to single gel system (C-S-H or N-A-S-H), and there are different degrees of performance short board. If the ordinary Portland cement system (C-S-H gel) and the alkali-activated coal-based solid waste geopolymer system (N-A-S-H gel) are organically coordinated to form a C-S-H and N-A-S-H double gel interpenetrating network structure, it is possible to break through the performance limit of the conventional single gel system and provide a new green grouting reinforcement material for grouting reinforcement. In this regard, the current research has explored the partial replacement of cement materials by coal gangue and other coal-based solid wastes, but due to the limitations of the conventional coal gangue activation preparation process, the activity of the coal gangue components is insufficient (the general particle size D95 is greater than 150 μm), so the coal-based solid waste and cement are simply physically compounded, and the active components cannot be deeply coordinated, resulting in a significant decrease in the strength of the stone body when the coal-based solid waste content exceeds 20%, which restricts the engineering application. Therefore, it is urgent to break through the technical bottlenecks of efficient activation of coal-based solid waste and deep coordination and enhancement of C-S-H and N-A-S-H double gel, form a new green grouting reinforcement material system with high performance and low environmental load, and provide an innovative solution for the resource utilization of solid waste and the upgrading of grouting materials. SUMMARY

[0005] The present application aims to provide an alkali-activated ultra-fine coal-based solid waste-ultra-fine Portland cement double gel deep coordination grouting reinforcement material and a preparation method, which solves the problem of insufficient performance of the existing single gel system and realizes the green grouting goal of low cost, high efficiency and resource conservation.

[0006] To solve the above technical problems, the present application is realized by the following technical scheme:

[0007] The present application is an ultra-fine coal-based solid waste green grouting material based on double gel coordination, which is composed of ultra-fine coal-based solid waste powder, ultra-fine Portland cement, polycarboxylate superplasticizer composite functional admixture and water, and the mass fractions of the components are as follows:

[0008] The ultra-fine coal-based solid waste powder is 40-60 parts, the particle size D95 is less than or equal to 10 μm, the total content of amorphous SiO2 and Al2O3 is greater than or equal to 70%, and the Si / Al ratio is 2.0-3.0;

[0009] The ultra-fine Portland cement is 30-50 parts, the particle size D95 is less than or equal to 10 μm, and the C3S content is greater than or equal to 55%;

[0010] The polycarboxylate superplasticizer has a mass of 1%-2% of the total mass of the cementitious materials;

[0011] The composite functional admixture contains 3%-5% calcium sulphoaluminate and magnesium oxide composite expansion agent, 0.1%-0.3% sodium gluconate retarder, and 2%-3% calcium nitrate early strength agent;

[0012] water, water mass / (high-activity ultra-fine coal-based solid waste powder + ultra-fine portland cement + Ca / Si ratio regulator) mass = 0.35-0.55;

[0013] The Ca / Si ratio of the ultra-fine coal-based solid waste powder and the ultra-fine portland cement composite system is 1.0-1.5, forming an interpenetrating network structure in which C-S-H gel and N-A-S-H gel are interwoven.

[0014] As a preferred technical solution of the present application, the ultra-fine coal-based solid waste powder is prepared by a multi-stage synergistic activation process, including the following steps:

[0015] Raw material screening: screened according to XRD detection to meet A l2 O3≥20%, SiO3≥40% coal gangue;

[0016] High-pressure roller milling: crushed to a particle size of ≤5 mm at a pressure of 3.0-6.0 MPa to form a three-dimensional microcrack structure;

[0017] High-temperature calcination: calcined at 600-800°C for 1-2 hours, and rapidly gas-quenched in a nitrogen atmosphere;

[0018] Ultra-fine grinding: planetary ball mill gradient speed grinding for 2 hours, D95≤10μm;

[0019] Component regulation: analyze the amorphous SiO2 and Al2O3 content by XRD and FT-IR testing technology, and adjust the components in proportion to Si / Al=2.0-3.0;

[0020] Alkali activator dry mixing pre-catalysis: configure a solid composite alkali activator, and mix the ultra-fine coal-based solid waste powder with the solid composite alkali activator by dry pre-activation process.

[0021] As a preferred technical solution of the present application, in the above component regulation step, specifically:

[0022] When amorphous SiO2+Al2O3<70%, repeat the high-temperature calcination and ultra-fine grinding steps;

[0023] When the total content of amorphous SiO2+Al2O3≥70%, adjust the components according to the Si / Al ratio;

[0024] When Si / Al<2.0, add ultra-fine silica fume to increase the Si proportion for component adjustment, and when Si / Al>3.0, add ultra-fine mineral powder to increase the Al proportion for component adjustment, so that the Si / Al ratio meets 2.0-3.0.

[0025] As a preferred technical scheme of the present application, the content of the solid composite alkali activator in the dry mixing pre-catalysis step of the alkali activator is 5% to 12% of the mass of the ultra-fine coal-based solid waste powder.

[0026] As a preferred technical scheme of the present application, in the dry mixing pre-catalysis step of the alkali activator, the solid composite alkali activator is configured by adjusting the compounding of anhydrous sodium silicate and ultra-fine sodium hydroxide according to the modulus M,

[0027] The modulus of the alkali activator is selected according to the Si / Al ratio of 2.0 to 3.0:

[0028] When Si / Al = 2.0 to 2.5, M = 1.0 to 1.2;

[0029] When Si / Al = 2.5 to 3.0, M = 1.2 to 1.5.

[0030] As a preferred technical scheme of the present application, the addition condition of the Ca / Si ratio adjusting agent is as follows:

[0031] When Ca / Si > 1.5, the amount of ultra-fine Portland cement is reduced or 5 to 10 parts of ultra-fine silica fume is added;

[0032] When Ca / Si < 1.0, the amount of ultra-fine Portland cement is increased or 5 to 10 parts of ultra-fine mineral powder is added.

[0033] The present application also provides a preparation method of the above-mentioned ultra-fine coal-based solid waste green grouting material based on the synergy of double gels, which comprises the following steps:

[0034] S1 weighing each component according to the weight parts;

[0035] S2 dry pre-activation mixing of the ultra-fine coal-based solid waste powder and the solid composite alkali activator;

[0036] S3 adding ultra-fine Portland cement, ultra-fine mineral powder or ultra-fine silica fume, polycarboxylic acid water reducer, composite functional additive, and adding an appropriate amount of water for stirring, controlling the stirring speed and time, so that the slurry reaches the required apparent viscosity.

[0037] As a preferred technical scheme of the present application, the S3 step is specifically operated as follows: first, 70% to 80% of the total water is added, and stirring is carried out at 800 to 1000 rpm for 2 to 3 min; then the remaining water is added, and stirring is carried out at 1500 to 2000 rpm for 5 to 8 min, and the apparent viscosity of the slurry is controlled to be less than or equal to 0.5 Pa·s.

[0038] The present application has the following beneficial effects:

[0039] 1. The preparation of high-activity ultra-fine coal-based solid waste powder material is realized through a multi-stage synergistic activation process of "raw material screening-mechanical crushing-high temperature calcination-ultra-fine grinding-component optimization-chemical catalysis"; compared with pure geopolymer grouting material (which relies on fly ash or slag raw materials), the bottleneck of using coal gangue as raw material is solved.

[0040] 2. Through accurate component proportioning design (Si / Al ratio, Ca / Si ratio), C-S-H and N-A-S-H double gel interweaving is realized to form a dense interpenetrating network, and the early strength and long-term strength of the stone body develop in balance.

[0041] 3. The process has high fault tolerance, and compared with pure geopolymer grouting material which needs precise control of activator modulus and curing conditions, the cement (C-S-H) gel buffer in the double gel system can reduce the sensitivity of alkali activator dosage.

[0042] 4. The environmental protection is excellent, and by using coal-based solid waste to replace cement in large amount, the utilization of solid waste is realized while the carbon emission of cement consumption is significantly reduced.

[0043] Of course, implementing any product of the present application does not necessarily need to achieve all the advantages described above at the same time. BRIEF DESCRIPTION OF DRAWINGS

[0044] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings needed for the description of the embodiments will be briefly introduced as follows. Obviously, the drawings in the following description are only some embodiments of the present application, and other drawings can be obtained by those skilled in the art without creative labor.

[0045] Figure 1 The preparation flow chart of the material of the present application;

[0046] Figure 2 The C-S-H and N-A-S-H double gel interpenetrating network structure diagram of the material of the present application;

[0047] Figure 3 The influence of Ca / Si ratio of the adjusting agent on the strength development in the embodiment. DETAILED DESCRIPTION

[0048] The technical solutions in the embodiments of the present application will be described clearly and completely in combination with the drawings of the embodiments of the present application. Obviously, the described embodiments are only some embodiments of the present application, not all. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative labor are within the scope of protection of the present application.

[0049] As Figure 1 , Figure 2、 Figure 3 The application provides a green grouting material based on double-gel synergy of ultra-fine coal-based solid waste, which is composed of a double-gel material of an ultra-fine coal-based solid waste powder and an ultra-fine portland cement, a Ca / Si ratio adjusting agent, a polycarboxylate superplasticizer composite functional additive and water.

[0050] S1, each component is weighed according to weight parts;

[0051] S2, the ultra-fine coal-based solid waste powder material is mixed with the ultra-fine portland cement by dry pre-activation;

[0052] S3, the composite alkali activator and the additive are added, and an appropriate amount of water is added for stirring, the stirring speed and time are controlled, and the slurry reaches the required apparent viscosity.

[0053] One specific embodiment of the application is as follows:

[0054] Preparation of the ultra-fine coal-based solid waste powder material

[0055] A multi-stage synergistic activation process of "raw material selection-mechanical crushing-high temperature calcination-ultra-fine grinding-component optimization-chemical catalysis" is adopted to prepare the high-activity ultra-fine coal-based solid waste powder material, which breaks through the low-activity bottleneck of coal-based solid waste, and the main preparation steps are as follows:

[0056] Coal gangue raw material selection: a certain amount of coal gangue raw material is selected according to the industry sampling detection standard, the basic component characteristics of the coal gangue raw material are tested by X-ray diffraction (XRD) technology, and the coal gangue raw material is selected according to the basic component requirement that the content of Al2O3 is greater than or equal to 20% and the content of SiO2 is greater than or equal to 40%; the qualified raw material enters the next step of processing, otherwise the coal gangue raw material is selected again.

[0057] High-pressure roller mill mechanical crushing: a high-pressure roller mill (pressure 3.0-6.0 MPa) is adopted to pretreat the coal gangue, and the coal gangue is crushed to a particle size of not more than 5 mm; at the same time, the coal gangue particles produce a three-dimensional network microcrack structure through the action of a "compression-shearing" composite stress field, the microcrack density is not less than 50 pieces / mm3 (tested by micron CT scanning), the specific surface area is increased, and the high-temperature thermal activation and ultra-fine grinding activation effects in the subsequent steps are improved.

[0058] High-temperature calcination thermal activation: the crushed coal gangue is calcined at a high temperature of 600-800 DEG C for 1-2 hours, and is combined with a rapid gas quenching cooling system (cooling rate greater than or equal to 200 DEG C / min), the gas quenching cooling system adopts a nitrogen medium, the oxygen content is controlled to be less than 5%, so as to prevent the oxidation of active components and inhibit the generation of mullite and other inert crystal phases. The calcination adopts a waste heat reuse technology to reduce the energy consumption of coal gangue thermal activation.

[0059] Ultrafine grinding activation: After the calcined coal gangue is cooled, 5% Na2CO3 grinding aid is added, and a planetary ball mill is used for ultrafine grinding (rotation speed gradient adjustment of 300→600→800 rpm, ball-to-material ratio of 10:1) for 2 h to destroy the crystal structure and release active Si / Al, forming an active powder with a particle size D95≤10 μm.

[0060] Component compounding optimization: The amorphous SiO2+Al2O3 content in the ultrafine coal-based solid waste powder formed above is analyzed by X-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FT-IR) and other test technologies. If the total content of amorphous SiO2+Al2O3 is <70%, the steps (3) and (4) for thermal activation and ultrafine activation treatment need to be repeated. If the total content of amorphous SiO2+Al2O3 is ≥70%, the components are fine-tuned according to the Si / Al ratio (the amount of SiO2 in the powder / the amount of Al2O3). If the ratio of the two is Si / Al=2.0-3.0, it directly enters the next step. Otherwise, the components of the ultrafine coal-based solid waste powder need to be compounded and fine-tuned so that the Si / Al ratio meets the optimal range. The specific method is as follows: ① If Si / Al <2.0, ultrafine silica fume is added to increase the Si proportion for component fine-tuning; ② If Si / Al >3.0, ultrafine mineral powder is added to increase the Al proportion for component fine-tuning.

[0061] Alkali activator dry mixing pre-catalysis: A solid composite alkali activator is prepared by compounding anhydrous sodium silicate (Na2SiO3·nH2O, n≤0.5) and ultrafine sodium hydroxide (D50≤15 μm) according to the modulus (molar ratio M=SiO2 / Na2O). The modulus is selected according to the Si / Al ratio of the ultrafine coal-based solid waste powder prepared above: ① When Si / Al=2.0-2.5, M=1.0-1.2 is selected to promote Al dissolution with low modulus; ② When Si / Al=2.5-3.0, M=1.2-1.5 is selected to enhance Si-O network polymerization with high modulus. The ultrafine coal-based solid waste powder and the solid composite alkali activator are pre-activated by dry mixing (5-8 min high-speed mixing) to make Na⁺, SiO3²⁻, and other ions uniformly distributed on the surface of the powder particles, forming a high-activity ultrafine coal-based solid waste powder material with self-catalytic properties. The dosage of the solid composite alkali activator is 5%-12% of the mass of the ultrafine coal-based solid waste powder. Excessive amount may cause alkali-aggregate reaction.

[0062] Ultrafine coal-based solid waste-ultrafine portland cement double-gel injection material configuration

[0063] Using the highly active ultrafine coal-based solid waste powder material and ultrafine silicate cement prepared above as the main materials, combined with necessary additives, the deep synergy of dual gels (CSH and NASH) is achieved by precisely adjusting the Ca / Si ratio (total CaO / total SiO2 in the material system). The components and proportions of the dual gel grouting material system are precisely designed as follows:

[0064] Highly active ultrafine coal-based solid waste powder: 40-60 parts, providing NASH gel framework;

[0065] Ultrafine silicate cement: 30-50 parts, material particle size D95≤10μm, C3S content≥55%, used to generate CSH gel;

[0066] like Figure 2 As shown: (3) Ca / Si ratio optimization adjustment: The Ca / Si ratio of the above-mentioned high-activity ultrafine coal-based solid waste powder and ultrafine silicate cement composite system directly affects the synergistic effect of the double gel depth. The optimal ratio is Ca / Si = 1.0 to 1.5. If Ca / Si > 1.5, it is beneficial to the rapid generation of CSH, but excessive Ca²⁺ will inhibit NASH polymerization. At this time, it is necessary to reduce the amount of ultrafine silicate cement in (2) or add an appropriate amount of ultrafine silica fume (to supplement the high-activity silicon source). If Ca / Si < 1.0, the CSH gel formation is hindered and the early strength is insufficient. It is necessary to increase the amount of ultrafine silicate cement in (2) or add an appropriate amount of ultrafine mineral powder (to supplement the high-activity Ca²⁺ source). According to the above, the amount of ultrafine silica fume / ultrafine mineral powder that needs to be added is generally 5 to 10 parts, and the particle size D95 ≤ 10 μm.

[0067] Polycarboxylate superplasticizer: 1% to 2% of the total mass of cementitious materials, to improve the fluidity of slurry;

[0068] Composite functional admixtures include expanding agents, retarders, and accelerators. The expanding agent uses a 3%–5% calcium sulfoaluminate and magnesium oxide composite system to compensate for the accelerated shrinkage of slurry aggregates under high alkalinity conditions; the retarder uses 0.1%–0.3% sodium gluconate to alleviate the accelerated setting caused by alkali activators; and the accelerator uses 2%–3% calcium nitrate to improve early strength.

[0069] Preparation of grout for dual-gel deep synergistic grouting reinforcement material

[0070] Slurry water-cement ratio: water mass / (mass of high-activity ultrafine coal-based solid waste powder + ultrafine silicate cement + ultrafine mineral powder) = 0.35~0.55;

[0071] Slurry preparation process: high activity ultrafine coal-based solid waste powder, ultrafine portland cement, ultrafine mineral powder, polycarboxylic acid water reducing agent, composite functional admixture and the like are added into a stirrer in turn, 70-80% of total water is added first, and stirring is carried out at a speed of 800-1000 rpm for 2-3 minutes; the remaining water is added, and stirring is continued at a speed of 1500-2000 rpm for 5-8 minutes, the apparent viscosity of the slurry is controlled to be not more than 0.5 Pa·s, and the permeability of the slurry in the microcracks is ensured.

[0072] As shown in Figure 3 The performance of the double-gel deep synergistic grouting reinforcing material is as follows: the above-mentioned ultrafine coal-based solid waste-ultrafine portland cement slurry forms a dense interpenetrating network of C-S-H and N-A-S-H double gels through the double-gel deep synergistic effect, and there is no crack in the interface area of the two; at the same time, the early and long-term strengths develop evenly, the 3d compressive strength is greater than or equal to 15 MPa, the 90d compressive strength is greater than or equal to 65 MPa, and the 90d porosity is less than or equal to 10%.

[0073] In the description of the present specification, the description of the terms "one embodiment", "example", "specific example" and the like means that the specific features, structures, materials or characteristics described in connection with the embodiment or example are included in at least one embodiment or example of the present application. In the present specification, the illustrative description of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0074] The preferred embodiments of the application disclosed above are only used to help explain the application. The preferred embodiments do not describe all the details, nor limit the application to the specific embodiments described. Obviously, many modifications and variations can be made according to the content of the present specification. The present specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the application, so that those skilled in the art can well understand and utilize the application. The application is limited only by the claims and their entire scope and equivalents.

Claims

1. A green grouting material based on dual gel synergy of ultrafine coal-based solid waste, characterized by, The super fine coal-based solid waste powder, the super fine portland cement, the polycarboxylate superplasticizer composite functional additive and water are included, and the mass fraction of each component is as follows: The super fine coal-based solid waste powder 40-60 parts, the particle size D95≤10 μm, the total content of amorphous SiO2 and Al2O3≥70%, and the Si / Al ratio is 2.0-3.0; The super fine portland cement 30-50 parts, the particle size D95≤10 μm, and the C3S content≥55%; The polycarboxylate superplasticizer, the mass is 1%-2% of the total mass of cementitious materials; The composite functional additive contains calcium sulphoaluminate and magnesium oxide composite expansion agent, sodium gluconate retarder and calcium nitrate early strength agent; The water, the water mass / (high activity super fine coal-based solid waste powder+super fine portland cement+Ca / Si ratio regulator) mass=0.35-0.55; The Ca / Si ratio of the super fine coal-based solid waste powder and the super fine portland cement composite system is 1.0-1.5, and the interpenetrating network structure of C-S-H gel and N-A-S-H gel interweaving is formed.

2. The dual gelation synergy based ultrafine coal-based solid waste green grout material as claimed in claim 1, wherein, The super fine coal-based solid waste powder is prepared by a multi-stage synergistic activation process, including the following steps: Raw material screening: XRD detection is used to screen the coal gangue with Al2O3≥20% and SiO2≥40%; High pressure roller grinding: crushed to a particle size≤5 mm under a pressure of 3.0-6.0 MPa to form a three-dimensional microcrack structure; High temperature calcination: calcined at 600-800 ℃ for 1-2 hours, and rapidly gas quenched under nitrogen atmosphere; Super fine grinding: planetary ball mill gradient speed grinding for 2 hours, D95≤10 μm; Component regulation: XRD and FT-IR testing technologies are used to analyze the content of amorphous SiO2 and Al2O3, and the components are finely adjusted according to the Si / Al ratio of 2.0-3.0; Alkali activator dry mixing pre-catalysis: solid composite alkali activator is prepared, and the super fine coal-based solid waste powder and the solid composite alkali activator are mixed by dry pre-activation process.

3. The dual gelation synergy based ultrafine coal-based solid waste green grout material as claimed in claim 2, wherein, In the above component regulation step, specifically: When the amorphous SiO2+Al2O3<70%, repeat the high temperature calcination and super fine grinding steps; When the total content of amorphous SiO2+Al2O3≥70%, the components are finely adjusted according to the Si / Al ratio; When Si / Al<2.0, the Si proportion is increased by adding super fine silica fume for component fine adjustment, and when Si / Al>3.0, the Al proportion is increased by adding super fine ore powder for component fine adjustment, so that the Si / Al ratio meets 2.0-3.

0.

4. The dual gelation synergy based ultrafine coal-based solid waste green grout material as claimed in claim 3, wherein, The dosage of the solid composite alkali activator in the alkali activator dry mixing pre-catalysis step is 5%-12% of the mass of the super fine coal-based solid waste powder.

5. The dual gelation synergy based ultra-fine coal-based solid waste green grout material as claimed in claim 4, wherein, In the alkali activator dry mixing pre-catalysis step, the solid composite alkali activator is prepared by adjusting the compounding of anhydrous sodium silicate and super fine sodium hydroxide according to the modulus M, The alkali activator modulus is selected according to the Si / Al ratio of 2.0-3.0: When Si / Al=2.0-2.5, M=1.0-1.2; When Si / Al=2.5-3.0, M=1.2-1.

5.

6. The dual gelation synergy based ultra-fine coal-based solid waste green grout material as claimed in claim 1, wherein, Also included are optional components: Ca / Si ratio adjuster: add 5-10 parts of superfine silica fume or superfine mineral powder according to system requirements, for regulating the Ca / Si ratio of the system to 1.0-1.5; The addition conditions of the Ca / Si ratio adjuster are as follows: When Ca / Si>1.5, reduce the amount of superfine Portland cement or add 5-10 parts of superfine silica fume; When Ca / Si<1.0, increase the amount of superfine Portland cement or add 5-10 parts of superfine mineral powder.

7. A process for the preparation of dual gel synergy based ultrafine coal-based solid waste green grout material as claimed in any one of claims 1-6, wherein, The method comprises the following steps: S1: weigh each component according to weight parts; S2: dry pre-activation mixing of superfine coal-based solid waste powder and solid composite alkali activator; S3: add superfine Portland cement, superfine mineral powder or superfine silica fume, polycarboxylic acid water reducer, and composite functional admixture, and add an appropriate amount of water for stirring, control the stirring speed and time, and make the slurry reach the required apparent viscosity.

8. The process for the preparation of dual gel synergy based ultra-fine coal-based solid waste green grout material as claimed in claim 7, wherein, The specific operation of the S3 step is as follows: first add 70%-80% of the total water amount, stir at 800-1000 rpm for 2-3 min; then add the remaining water, stir at 1500-2000 rpm for 5-8 min, and control the apparent viscosity of the slurry to be ≤0.5 Pa·s.